THE ROLE OF EXPOSURE CONDITION IN THE EFFECTIVENESS OF EXPLICIT CORRECTION. Issue 1 (26th June 2015) - Yilmaz, Yucel
Abstract : This article reports on a study that investigated the effects of two feedback exposure conditions on the acquisition of two Turkish morphemes. The study followed a randomized experimental design with an immediate and a delayed posttest. Forty-two Chinese-speaking learners of Turkish were randomly assigned to one of three groups: receivers, nonreceivers, and control. All learners performed three communication games with a Turkish native speaker in which their errors on the Turkish plural and locative morphemes were treated according to their group assignment. The receivers' errors were corrected through explicit correction. The nonreceivers were allowed to hear the feedback provided to the receivers; however, they did not receive feedback on their own errors. The learners in the control group neither received feedback on their own errors nor were allowed to hear the feedback other learners received. Results indicated that feedback exposure condition has an effect on the extent to which learners benefit from feedback but that this effect may be moderated by linguistic structure.